Educating in Utilization of Household Waste into Eco-enzymes and Eco-bricks at Densely Populated Community in Bandung Regency (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Eco-enzymes are a natural alternative to harmful synthetic chemicals in the home. Changing organic kitchen waste from vegetable and fruit waste into household and environmental recycling materials can help solve the waste problem. Eco-enzyme liquid has many uses, such as washing dishes, clothes, floors, hair, body wash, hand sanitizer, body detox, air freshener, radiation blocker, pool cleaner, pet and organic fertilizers and pesticides that can be made from organic waste. This community service program aimed to increase public awareness and sensitivity to the problems that were found in the environment, provide ideas for entrepreneurship such as the utilization of waste in the form of eco enzymes, and eco brick. The socialization activities were carried out through presentations, discussions, and demonstrations of making eco enzymes, as well as distributing questionnaires to find out the increase in the level of public understanding before and after the activity was carried out. The questionnaire results showed that people's knowledge about the use of organic waste to make eco enzymes increased after participating in extension activities, as well as the community's interest in processing organic waste into eco enzymes and using them in daily life